THE ANALYSIS OF WOMEN ROLE’S IN THE SMALL INDUSTRY TO FAMILY ECONOMIC STABILITY - Wenni Anggita (Jurnal Riset Akuntansi Terpadu, 2018)
This research combines a quantitative and qualitative approach so that in this research the analytical approach uses descriptive mix method. It is intended that this research can touch on things that are not likely to be found by statistical analysis. This research combines sociology and economic science in general, it can be seen from the issues raised in this study that examines women role’s in the small industry that will be combined with the matching family economy. The results of this study showed that the role of women in the small industry is very impact on the family economic stability. In addition, the benefits perceived by the small industry is improving the economy in Sungai Selan Village. The full support of the government also helps in this process of empowering women toward economically independent women who will improve the family economic stability.